1994
DOI: 10.1080/10519999408225557
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model for estimating thermophysical and strength parameters of the cooled pipe with the twisted tape under asymmetric heating by a pulse of external heat flux

Abstract: The main statements of the model are formulated from the statement of a general problem on determination of a temperature field in the material of a finite length-pipe, single-side heated by an external quasi-stationary heat flux with the high power density, q., = 10 MW/m2, and with the heat removal by a coolant from the parts of wetted pipe cross-section perimeter in the surface boiling regime, as well as under forced turbulent heat removal without phase transitions in the coolant.The obtained relationships a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Naumov et al [65,66] used a mathematical model for an adiabatic cross-section to study the pulsed asymmetric heating of pipes by an external heat flux and calculated the thermophysical parameters of cooled pipes containing twisted tapes within the collector of deviated ions in the T-15 tokamak injection system. Yokoya et al [68] demonstrated a novel use of twisted tapes in controlling the flow in a continuous casting mould and refining process.…”
Section: Twisted Tape In Turbulent Flowmentioning
confidence: 99%
“…Naumov et al [65,66] used a mathematical model for an adiabatic cross-section to study the pulsed asymmetric heating of pipes by an external heat flux and calculated the thermophysical parameters of cooled pipes containing twisted tapes within the collector of deviated ions in the T-15 tokamak injection system. Yokoya et al [68] demonstrated a novel use of twisted tapes in controlling the flow in a continuous casting mould and refining process.…”
Section: Twisted Tape In Turbulent Flowmentioning
confidence: 99%
“…The passive techniques are advantageous compared with the active techniques because the swirl inserts manufacturing process is simple and can be easily employed in an existing heat exchanger. Moreover the passive techniques can play an important role in the heat transfer augmentation if a proper configuration of the insert is being selected depending on working conditions that have been reported in the literature [1][2][3][4][5][6][7][8][9]. Due to advances in computer software, the Computational Fluid Dynamics (CFD) modelling technique was developed as a powerful and effective tool for more understanding the hydrodynamics of heat transfer when using twist tape inserts.…”
Section: Introductionmentioning
confidence: 99%